(untitled) (University of Khartoum Journal of Agricultural Sciences, 2022)
Bacterial spot caused by Xanthomonas vesicatoria is considered to be a major constraint of tomato production all over the world in particular warmer and humid parts.A disease disorder was reported in autumn season 2015within the Blue Nile State in Sudanaffecting all aerial parts of tomato plant. Symptomatic tomato leaves were collected and sent to Plant Pathology Laboratory, Faculty of Agriculture, University of Khartoum. An investigation on whether a phytopathogen was associated with symptoms of bacterial spots damage on tomato was conducted.The pathogen was isolated and characterized morphologically, biochemically and at molecular level. The bacterium wasidentified as Xanthomonaseuvesicatoria and confirmed by PCR and sequence analysis of the 16S RNA gene (GenBank Accession Nos MH047248, MH051263 and MG686236).The disease incidence was remarkably high in ALrosserisand Aldamazein which recorded 49.27 and 52.17%, respectively, while the disease severity was 28.28 and 30.32%, respectively. To our knowledge, this is the first report of Xanthomonaseuvesicatoria causing bacterial spot disease in tomato in Sudan.